(untitled) (Annals of Medical Research, 2021)
Aim: Bupivacaine, which is widely used in neuraxial anesthesia, may lead to negative inotropic effect and arrhythmias. In this study, our objective is to evaluate the effects of bupivacaine on corrected QT interval (QTc) and P wave dispersion in epidural anesthesia and to compare them with those in spinal anesthesia. Material and Methods: Ninety patients (59 male, 31 female) who applied neuraxial anesthesia for unilateral inguinal hernia repair were randomly allocated into two groups: Group S (Spinal, n = 49), Group E (Epidural, n = 41). Neuraxial anesthesia was performed by bupivacaine in both groups. We calculated heart rate, QT interval, corrected QT interval and P wave dispersion from electrocardiography, before anesthesia and after the operation. Results: Postoperative QT interval was significantly longer than preoperative value in both groups (preoperative 0.388 sec in Group S and Group E versus, postoperative 0.407 sec in Group S and 0.397 sec in Group E), (p=0.001). Postoperative QTc prolongation was significantly higher in Group S, but there was no statistically significant difference between the groups (preoperative 0.418 sec versus, postoperative 0.424 sec in Group S), (p = 0.129). Preoperative and postoperative P wave dispersion value revealed no statistically significant differences in both inter- and intragroup comparisons. Conclusion: Bupivacaine caused a postoperative QTc interval prolongation in spinal and epidural anesthesia, which did not reach levels that were regarded as risky for ventricular arrhythmias despite being more prominent in the spinal anesthesia group compared with the epidural anesthesia group.